Regression-Based Normative Data for Children From Latin America: Phonological Verbal Fluency Letters M, R, and P. (January 2021) - Rivera, Diego; Olabarrieta-Landa, Laiene; Van der Elst, Wim; Gonzalez, Isabel; Ferrer-Cascales, Rosario; Peñalver Guia, Ana Ivis; Rodriguez-Lorenzana, Alberto; Galarza-del-Angel, Javier; Irías Escher, María José; Arango-Lasprilla, Juan Carlos
This study is part of a larger project to generate norms for letter verbal fluency test (VFT) in 3, 284 children from nine Latin American countries. The letter VFT (letters M, R, and P) was administered and multiple linear regressions, including age, age 2, MPE (mean parental education), MPE 2, sex, and interactions were used as predictors. Results showed significant differences across countries for all scores. Age affected scores linearly except for Ecuador (P-letter), in which a quadratic effect was found. Scores increased linearly as a function of MPE, with the exception of Mexico (R-letter), in which a quadratic effect was found. Age by MPE (M- and P-letters), and age by MPE 2 (R-letter) interactions were found in Mexico. Sex had an impact on letter R in Cuba, and letter P in Ecuador and Paraguay. Age 2 by sex interaction was found in Ecuador (P-letter). These norms will be useful for clinical neuropsychologists in these countries to evaluate their patients' verbal fluency.